Validating Organizational Effectiveness: Exploring Criteria for Exemplary and Outstanding Local Conferences in the North American Division - Brown Sr., Theodore (Archives of Business Research, 2019)
ABSTRACT Organizations in various sectors of diverse domestic and global industries (profit and not-for-profit) (public or private) such as business, education, government, healthcare, military, religious, etc. operate in very competitive environments that require the highest levels of excellence in operational standards. Indicators of outstanding organizations (germane to a particular industry) may tend to use measurements such as an entity’s certified audit reports; competitive advantage; financial indicators, market share; growth, expansion and/or retention; profitability; shareholder investment returns; stakeholder engagement and customer satisfaction surveys. Benchmarks to achieve these standards may also be found in gold star instruments such as the Malcolm Baldridge Award, Good-to-Great Organizations and Industry Best Practices. The basis for this qualitative exploration was instigated by sentiments that Seventh-day Adventist (SDA) local conferences may also aspire to emulate standards of excellence that are expected and exemplified in other exemplary organizations. Three critical questions this study will address are: (1) What are possible criteria and standards of organizational excellence and effectiveness? (2) What comprises an organization’s effectiveness system? (3) What are the attributes of an effective and efficient organization? A qualitative design was utilized with data for this study selected, collected and analyzed (coding, patterns, trends and themes) from extensive open-ended questionnaires to targeted populations of NAD and Union conference CEOs (Chief Executive Officers/Presidents), CAOs (Chief Administrative Officers/Executive Secretaries) and CFOs (Chief Financial Officers/Treasures) N=30 throughout Canada and the United Stated of America (USA) with a participant response rate of N=13 or 43%. Discussion, Implications, Conclusion and Recommendations are also discussed.